Out of the Shtetl : Making Jews Modern in the Polish Borderlands - Sinkoff, Nancy (Book collections on Project MUSE., 2020)
"In Out of the Shtetl: Making Jews Modern in the Polish Borderlands, Nancy Sinkoff examines some of the thinkers, particularly Mendel Lefin and Joseph Perl, who as part of the Jewish Enlightenment movement (Haskalah) of the nineteenth century attempted to articulate a vision and plan for how the Jews of Eastern Europe could become modern while remaining Jews."--Provided by publisher.